Peran Kompetensi Literasi Digital Terhadap Konten Hoaks dalam Media Sosial - Najla Amaly; Armiah Armiah (UIN Antasari Banjarmasin, 2021)
The rise of cases of spreading hoax news in Indonesia is a negative impact of the development of digital technology and social media which is not balanced with people's digital literacy. Cases of fake and fake news (Hoax) are increasing in Indonesia every year. Kominfo for 24 hours 7 days monitors cyber crime on social media related to hoax information, and almost every day finds disinformation on social media. Tackling the spread of negative content on social media requires digital media literacy skills. However, the Insight Center data survey shows that the digital media literacy of the community is still low, where the national digital literacy index level is still at a score of 3.47 where digital literacy is at the middle level. The survey also shows that the ability to process information, data literacy and critical thinking still has a low score. This journal aims to analyze the digital literacy competence of the community to deal with hoax news content on social media.